Keyword Based Efficient Web Crawler for Next Generation Semantic Web - Sheetal; Bansal, Megha (International Journal of Computer Sciences and Engineering, 2014)
This paper will be implement Ontology Based Search Using Semantic Web. The method of web crawling with filter is used. This approach is query based approach using Jena API. The proposed approach solves the problem of revisiting web pages by crawler. The Semantic Web is an extension of the current Web that allows the meaning of information to be precisely described in terms of well-defined vocabularies that are understood by people and computers.